Detail in contemporary residential architecture - McLeod, Virginia (London : Laurence King Publishing, 2007)
Presents an analysis of both the technical and the aesthetic importance of details in the development of contemporary residential architecture, providing a study of the trends in detailing. This work features many of the worlds most highly acclaimed architects.
Introduction; Concrete; Glass; Masonry; Steel; Timber; Aluminum, Bamboo, Plastic, Rubber, and Straw; Directory of Details; Directory of Architects; Index; Picture Credits.
Includes index.
Keywords: Architecture, Domestic -- Designs and plans; Architecture -- Details